2016
DOI: 10.1063/1.4947203
|View full text |Cite
|
Sign up to set email alerts
|

High-current operation of vertical-type organic transistor with preferentially oriented molecular film

Abstract: A high-performance vertical-type organic transistor has been fabricated using bis(l,2,5-thiadiazolo)-p-quinobis(l,3-dithiole) (BTQBT) for the channel layer. The BTQBT molecules are oriented horizontally, with the molecular plane of each monolayer parallel to the substrate. The π–π stacking direction of the BTQBT molecules is aligned with the carrier transport direction in this vertical transistor. The modulated drain current density exceeded 1 A cm−2 upon the application of a gate voltage of less than 5 V. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Indeed, several electric measurements and theoretical calculation results have supported the occurrence of band transport in the solid-state BTQBT [3][4][5][6]. A number of studies have addressed the usage of such promising properties of BTQBT for high-mobility organic electronic devices [7][8][9][10][11]. Among these, since BTQBT molecules tend to stack on various substrate surfaces lying their molecular planes parallel to the surface and so the electric conduction along the surface normal direction is the most favorable [12][13][14], transistor devices of a vertical architecture (static induction transistors) [15][16][17][18] are considered to be the most direct way of making use of the band transport nature of BTQBT.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, several electric measurements and theoretical calculation results have supported the occurrence of band transport in the solid-state BTQBT [3][4][5][6]. A number of studies have addressed the usage of such promising properties of BTQBT for high-mobility organic electronic devices [7][8][9][10][11]. Among these, since BTQBT molecules tend to stack on various substrate surfaces lying their molecular planes parallel to the surface and so the electric conduction along the surface normal direction is the most favorable [12][13][14], transistor devices of a vertical architecture (static induction transistors) [15][16][17][18] are considered to be the most direct way of making use of the band transport nature of BTQBT.…”
Section: Introductionmentioning
confidence: 96%
“…Among these, since BTQBT molecules tend to stack on various substrate surfaces lying their molecular planes parallel to the surface and so the electric conduction along the surface normal direction is the most favorable [12][13][14], transistor devices of a vertical architecture (static induction transistors) [15][16][17][18] are considered to be the most direct way of making use of the band transport nature of BTQBT. In fact, Fukagawa and coauthors reported high current density at relatively low gate voltages in vertical transistor devices based on BTQBT attached to polycrystalline Au electrodes [10]. To achieve a mature understanding of the working mechanisms in BTQBTbased vertical transistor devices, clear insights into the electronic (band) structures at the interface between BTQBT and the Au electrode and of the solid-state BTQBT itself are indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for conventional organic field-effect transistors (OFETs) sharing similar device configurations to c-OECTs, it has long been established that edge-on orientation can boost mobility. [19,20] Interestingly, Fukagawa et al demonstrated that when the conventional planar OFET goes vertical, its preferential orientation changes to face-on accordingly, [21] which can be summarized as a general rule for vertical OFETs. [22] All these relevant studies hint that an appropriate match between crystallite orientation and device architecture may be crucial in achieving high-performance OECTs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19,20 ] Interestingly, Fukagawa et al. demonstrated that when the conventional planar OFET goes vertical, its preferential orientation changes to face‐on accordingly, [ 21 ] which can be summarized as a general rule for vertical OFETs. [ 22 ] All these relevant studies hint that an appropriate match between crystallite orientation and device architecture may be crucial in achieving high‐performance OECTs.…”
Section: Introductionmentioning
confidence: 99%
“…Compilation of maximum current densities achieved versus on–off ratio in vertical organic transistors …”
Section: Introduction: Vertical Versus Lateral Organic Transistorsmentioning
confidence: 99%